Penyuluhan Peningkatan Kesehatan Lansia di Penyakit Paliatif Terhadap Perubahan Fisik dan Spiritual - Andrianto, M. Bagus; Yanti, Lussyefrida; Nopiawati, Nopiawati (Jurnal Pengabdian, 2024)
Old age is a natural process that everyone experiences and cannot be avoided. With the success of national development, especially in the health sector, which can be seen from the reduction in infant mortality and birth rates as well as improvements in public nutrition, the positive impact is an increase in life expectancy at birth in Indonesia, namely around 70 years. in 2000. In 2000, by 2020, it is estimated by the USA-Bureau of the Census that the number of elderly people in Indonesia will be around ± 29 million people. This is an illustration for all countries that thanks to advances in science and technology as well as advances in socio-economic conditions, life expectancy is increasing. Along with the success of improving the health status of the Indonesian people which has an impact on increasing life expectancy, this will have its own impact on the nation, state and on the welfare and health problems of the elderly themselves. Judging from the description above, special services are needed for the elderly in the areas of health, socio-economic, psychological, welfare and even spiritual, so there is a need to improve the health status and quality of life of the elderly. achieve a happy, prosperous and beneficial old age for family and community life in accordance with its existence in society